1984
DOI: 10.1523/jneurosci.04-11-02725.1984
|View full text |Cite
|
Sign up to set email alerts
|

Automatic gain control in the bat's sonar receiver and the neuroethology of echolocation

Abstract: The sensitivity of the echolocating bat, Eptesicus fuscus, to sonar echoes at different time delays after sonar emissions was measured in a two-choice echo detection experiment. Since echo delay is perceptually equivalent to target range, the experiment effectively measured sensitivity to targets at different ranges. The bat's threshold for detecting sonar echoes at a short delay of only 1.0 msec after emissions (corresponding to a range of 17 cm) was 36 dB SPL (peak to peak), but the threshold decreased to 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
168
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(174 citation statements)
references
References 45 publications
5
168
1
Order By: Relevance
“…We examined sonar emissions and found that bats, in both experiments, attacked all silent control and sound-producing moths with comparable echolocation patterns (Fig. 2C), similarly progressing through the approach, track, and terminal phases of attack (34).…”
Section: Resultsmentioning
confidence: 89%
“…We examined sonar emissions and found that bats, in both experiments, attacked all silent control and sound-producing moths with comparable echolocation patterns (Fig. 2C), similarly progressing through the approach, track, and terminal phases of attack (34).…”
Section: Resultsmentioning
confidence: 89%
“…Griffin first reported the dramatic increase in PPR by echolocating bats during the final attack of insect prey and termed it the buzz (Griffin, 1958;Griffin et al, 1960). Subsequent studies in echolocating bats have used changes in PPR to infer changes in the bat's behavioral state (Kick and Simmons, 1984;Schnitzler et al, 1987;Kalko, 1995). Foraging flight has been divided into four stages, according to the bat's vocal behavior: searching, approaching, tracking, and attacking (Kick and Simmons, 1984).…”
Section: Division Of Stages Of Bat Flight Based On Pprmentioning
confidence: 99%
“…Subsequent studies in echolocating bats have used changes in PPR to infer changes in the bat's behavioral state (Kick and Simmons, 1984;Schnitzler et al, 1987;Kalko, 1995). Foraging flight has been divided into four stages, according to the bat's vocal behavior: searching, approaching, tracking, and attacking (Kick and Simmons, 1984). The tracking and attack phases correspond to the terminal I and terminal II stages described by some authors (Kalko, 1995).…”
Section: Division Of Stages Of Bat Flight Based On Pprmentioning
confidence: 99%
See 1 more Smart Citation
“…Call intensity has a profound impact on ranging capabilities of the echolocation system, but very loud calls also carry substantial energy requirements, thus bats must efficiently regulate call intensity to match behapvioral contexts. It is well known that many bats decrease the intensity of their echolocation calls as they approach obstacles or prey [42,59,65,151]. This echo intensity compensation behavior is believed to optimize echo intensities for signal analysis within the auditory system [21,46,69], particularly during critical phases such as prey capture and navigating through cluttered spaces.…”
Section: Audio-vocal Integration In Bats and Other Mammalsmentioning
confidence: 99%